Hubungan antara Penggunaan Video Pembelajaran dengan Peningkatan Hasil Belajar Agama Islam pada Masa Pandemi Covid-19 Siswa Kelas 4 Sdn 001 Bontang Utara Tahun Pembelajaran 2020/2021 - Ihsan, Muh.; Ekaputra, Zeen Fu’ady (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
The task of a teacher as an educator greatly determines the success of their students, so they must be able to choose the appropriate models of learning, approaches, strategies, methods, and learning techniques. The purpose of this research is first, to determine whether there is a relationship between the use of instructional videos and the improvement of Islamic religious learning outcomes during the COVID-19 pandemic for 4th-grade students at SDN 001 Bontang Utara in the 2020/2021 academic year. Second, to determine the relationship between the use of instructional videos and the improvement of Islamic religious learning outcomes during the COVID-19 pandemic for 4th-grade students at SDN 001 Bontang Utara in the 2020/2021 academic year. This research was conducted at SDN 001 Bontang Utara for 2 months, from April 1st to June 2nd, 2021, with the participation of the school principal, teachers, students, and parents. In seeking accurate data on this issue, the researcher used a quantitative approach through observation, interviews, questionnaires, and structured documentation, which were then analyzed during the fieldwork and validated. The research results based on hypothesis testing obtained a value of 2.1799, which is greater than the t-table value of 1.993, thus it can be concluded that there is a significant relationship between instructional videos and the improvement of Islamic religious learning outcomes during the COVID-19 pandemic for 4th-grade students at SDN 001 Bontang Utara in the 2020/2021 academic year. This means that the use of instructional videos can be used in learning to improve the learning outcomes of Islamic religious subjects during the COVID-19 pandemic for 4th-grade students at SDN 001 Bontang Utara in the 2020/2021 academic year. To all education observers/managers and implementers, the researcher recommends further research and/or finding more influential learning media to improve student learning outcomes.